The Importance of State Policy in Ensuring International Harmony and Religious Tolerance in Uzbekistan - Niyazov Zafar Bakhodirovich (Zien Journals, 2023)
This article provides information about the importance of state policy in ensuring inter-ethnic harmony and religious tolerance in Uzbekistan. Also, the measures implemented in our country for religious tolerance and inter-ethnic harmony are reflected in the article
Keywords: Religion; religious tolerance; society; confession